2020
DOI: 10.1080/15538362.2020.1858470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vacuum and Modified Atmosphere Packaging on the Quality Attributes and Sensory Evaluation of Fresh Jujube Fruit

Abstract: Fresh jujube is recommended as a healthy and nutritious snack due to its low calorie and sugar content compared to dried jujube. But fresh jujube fruit has a short shelf life. This work aimed to study the effect of different initial modified atmosphere compositions on the quality properties and shelf-life of fresh jujube fruit. Experimental treatments were passive-MAP (control), vacuum, active-MAP1 (25% O 2 | 5% CO 2 ), and active-MAP2 (15% O 2 | 10% CO 2 ). Results indicated that vacuum and passive-MAP treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Also, as shown in Figure 1, vacuum packaging better retained the taste of pomegranate fruit, which is in line with the results of TSS, and TA in the present study. Similar results have been reported on the effect of vacuum packaging on preserving the sensory properties of jujube (Moradinezhad and Dorostkar, 2020) and litchi (Shah and Nath, 2006) fruit.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Also, as shown in Figure 1, vacuum packaging better retained the taste of pomegranate fruit, which is in line with the results of TSS, and TA in the present study. Similar results have been reported on the effect of vacuum packaging on preserving the sensory properties of jujube (Moradinezhad and Dorostkar, 2020) and litchi (Shah and Nath, 2006) fruit.…”
Section: Discussionsupporting
confidence: 87%
“…The results showed that during the storage period, the L* of fruit peel decreased or darkened, which indicates a decrease in the peel quality compared to harvest time. The researchers showed that the synthesis of ethylene, followed by senescence, causes the enzymes associated with oxidative reactions and ultimately leads to darkening (low L * value) of the color (Hasan et al, 2018;Morales et al, 2020) Moradinezhad and Dorostkar (2020) found that fresh jujube fruit under vacuum packaging had a higher L * value. They stated that vacuum packaging might inhibit enzymatic reac tions and delay the darkening of fruit color.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in ascorbic acid in fruit are influenced by fruit respiration. Previous studies have shown that vacuum packaging in jojoba fruit storage was effective in maintaining the ascorbic acid content [13]. Postharvest factors such as postharvest treatments, storage temperature and postharvest stress can also affect ascorbic acid content [14].…”
Section: Ascorbic Acidmentioning
confidence: 99%
“…As freshly harvested jujube has a high moisture content and high sugar content, it cannot be stored for more than ten days under ambient conditions (Song et al, 2020). Therefore, after harvesting, the moisture content (MC) of fresh jujube must be dried to 6.0% for long-term storage (Moradinezhad & Dorostkar, 2021). However, traditional drying methods, such as hot air (HA) drying, can easily cause deterioration of product quality.…”
Section: Introductionmentioning
confidence: 99%
“…Drying is an old and efficient technique for agricultural product preservation. Drying reduces the water activity of agricultural products to the safety range, and lower water activity facilitates lower transport costs, easier processing, and better quality to reduce the possibility of deterioration during storage (Moradinezhad & Dorostkar, 2021). For the past few years, HA drying has been widely used for the drying of fruits and vegetables given the advantage of its high efficiency.…”
Section: Introductionmentioning
confidence: 99%